Analisis Hukum Putusan Pengadilan Negeri Jayapura terhadap Tindak Pidana Kekerasan Seksual : Studi Kasus Putusan Nomor: 36/PID.B/ 2024/ PN. JAP - Farida Tuharea; Mukti Stoffel; Irsan Irsan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Sexual Violence Crime based on number: 36/PID. B/ 2024/ PN. JAP. In its decision, the Jayapura District Court has sentenced the defendant as regulated and threatened with criminal punishment in Article 285 of the Criminal Code and Law Number 8 of 1981 concerning the Criminal Procedure Law and other relevant laws and regulations, a legal review of the case is very necessary because for the case Article 6 letter b Jo Article 15 of Law Number 12 of 2022 concerning the Crime of Sexual Violence Jo Article 64 paragraph (1) of the Criminal Code can be applied. The purpose of this study is to examine the extent to which the verdict has fulfilled the principles of good justice, as well as the consistency of the application of the law to the crime of sexual violence. There is also a method used, namely normative-empirical legal research, which is a research method that combines or combines normative research methods with empirical research methods as part of the improvement of legal knowledge. The specification of this research is descriptive analytical, which reveals laws and regulations related to legal theories that are the object of research. The conclusion reached was that the Jayapura District Court's Decision on the Crime of Sexual Violence in the case of Decision Number: 36/PID. B/ 2024/ PN. JAP determined that thedefendant, who had been legally and convincingly proven, was guilty of committing the crime of